Modifiable Factors Associated with Uncontrolled Type 2 Diabetes Mellitus: Experience in a Tertiary Care Hospital of Bangladesh (BIRDEM Medical Journal, 2018)
Background: Diabetes mellitus is a non-communicable disease with increasing prevalence worldwide. The present study was done to identify the modifiable factors that were associated with the poor glycemic control in Bangladeshi type 2 diabetic patients attending in a tertiary care hospital.Methods: This cross-sectional study was conducted in the Department of Medicine, Sir Salimullah Medical College & Mitford Hospital (SSMC & MH), Dhaka from July 2014 to June 2015. A total of 140 adult type 2 diabetes mellitus patients were included in this study. Of them 70 patients had uncontrolled diabetes mellitus with glycated haemoglobin ³ 7% (group 1) and 70 patients with controlled diabetes mellitus (HbA1c< 7%) (group 2).Results: The present study demonstrated statistically significant difference regarding the mean age of both group 1 and group 2 [59.26±12.88 years and 55.24±11.52 years respectively (p